Inondations: pourra-t-on faire mieux la prochaine fois? - Maltais, Danielle; Gachon, Philippe; King, Suzanne; Raphoz, Marie; Ouarda, Taha (The Conversation, 2019)
Les inondations causent de lourds dommages tant économiques, sociaux qu'environnementaux, en plus d'avoir des effets sur la santé physique et psychologique des sinistrés.

Quantile-based downscaling of rainfall extremes: Notes on methodological functionality, associated uncertainty and application in practice - Hassanzadeh, Elmira; Nazemi, Ali; Adamowski, Jan; Nguyen, Truong-Huy; Van-Nguyen, Van-Thanh (Advances in Water Resources, 2019)

Evaluating Hydrologic Response in Tile‐Drained Landscapes: Implications for Phosphorus Transport - Macrae, M. L.; Ali, G. A.; King, K. W.; Plach, J. M.; Pluer, W. T.; Williams, M.; Morison, M. Q.; Tang, W. (Journal of Environmental Quality, 2019)
Phosphorus (P) loss in agricultural discharge has typically been associated with surface runoff; however, tile drains have been identified as a key P pathway due to preferential transport. Identifying when and where these pathways are active may establish high‐risk periods and regions that are vulnerable for P loss. A synthesis of high‐frequency, runoff data from eight cropped fields across the Great Lakes region of North America over a 3‐yr period showed that both surface and tile flow occurred year‐round, although tile flow occurred more frequently. The relative timing of surface and tile flow activation was classified into four response types to infer runoff‐generation processes. Response types were found to vary with season and soil texture. In most events across all sites, tile responses preceded surface flow, whereas the occurrence of surface flow prior to tile flow was uncommon. The simultaneous activation of pathways, indicating rapid connectivity through the vadose zone, was seldom observed at the loam sites but occurred at clay sites during spring and summer. Surface flow at the loam sites was often generated as saturation‐excess, a phenomenon rarely observed on the clay sites. Contrary to expectations, significant differences in P loads in tiles were not apparent under the different response types. This may be due to the frequency of the water quality sampling or may indicate that factors other than surface‐tile hydrologic connectivity drive tile P concentrations. This work provides new insight into spatial and temporal differences in runoff mechanisms in tile‐drained landscapes. Core Ideas Activation of surface runoff and tile flow differ with soil texture and season. Timing of flow path activation was used to infer hydrological processes. Connectivity between the surface and tiles exists on clay soil during growing season. Rapid connectivity between the surface and tiles occurs less frequently on loam.

Coupling the maximum overlap discrete wavelet transform and long short-term memory networks for irrigation flow forecasting - Mouatadid, Soukayna; Adamowski, Jan F.; Tiwari, Mukesh K.; Quilty, John M. (Agricultural Water Management, 2019)

A comparative study of fuzzy logic-based models for groundwater quality evaluation based on irrigation indices - Vadiati, Meysam; Nalley, Deasy; Adamowski, Jan; Nakhaei, Mohammad; Asghari-Moghaddam, Asghar (Journal of Water and Land Development, 2019)
Abstract Groundwater quality modelling plays an important role in water resources management decision making processes. Accordingly, models must be developed to account for the uncertainty inherent in the modelling process, from the sample measurement stage through to the data interpretation stages. Artificial intelligence models, particularly fuzzy inference systems (FIS), have been shown to be effective in groundwater quality evaluation for complex aquifers. In the current study, fuzzy set theory is applied to groundwater-quality related decision-making in an agricultural production context; the Mamdani, Sugeno, and Larsen fuzzy logic-based models (MFL, SFL, and LFL, respectively) are used to develop a series of new, generalized, rule-based fuzzy models for water quality evaluation using widely accepted irrigation indices and hydrological data from the Sarab Plain, Iran. Rather than drawing upon physiochemical groundwater quality parameters, the present research employs widely accepted agricultural indices (e.g., irrigation criteria) when developing the MFL, SFL and LFL groundwater quality models. These newly-developed models, generated significantly more consistent results than the United States Soil Laboratory (USSL) diagram, addressed the inherent uncertainty in threshold data, and were effective in assessing groundwater quality for agricultural uses. The SFL model is recommended as it outperforms both MFL and LFL in terms of accuracy when assessing groundwater quality using irrigation indices.

Human influence on Canadian temperatures - Wan, Hui; Zhang, Xuebin; Zwiers, Francis W. (Climate Dynamics, 2019)
Canada has experienced some of the most rapid warming on Earth over the past few decades with a warming rate about twice that of the global mean temperature since 1948. Long-term warming is observed in Canada’s annual, winter and summer mean temperatures, and in the annual coldest and hottest daytime and nighttime temperatures. The causes of these changes are assessed by comparing observed changes with climate model simulated responses to anthropogenic and natural (solar and volcanic) external forcings. Most of the observed warming of 1.7°C increase in annual mean temperature during 1948–2012 [90% confidence interval (1.1°, 2.2°C)] can only be explained by external forcing on the climate system, with anthropogenic influence being the dominant factor. It is estimated that anthropogenic forcing has contributed 1.0°C (0.6°, 1.5°C) and natural external forcing has contributed 0.2°C (0.1°, 0.3°C) to the observed warming. Up to 0.5°C of the observed warming trend may be associated with low frequency variability of the climate such as that represented by the Pacific decadal oscillation (PDO) and North Atlantic oscillation (NAO). Overall, the influence of both anthropogenic and natural external forcing is clearly evident in Canada-wide mean and extreme temperatures, and can also be detected regionally over much of the country.
MAG ID: 2793361457

Analysis of trends in annual streamflow to the Arctic Ocean - Durocher, Martin; Requena, Ana I.; Burn, Donald H.; Pellerin, Jennifer (Hydrological Processes, 2019)
Abstract There is increasing interest in the magnitude of the flow of freshwater to the Arctic Ocean due to its impacts on the biogeophysical and socio‐economic systems in the north and its influence on global climate. This study examines freshwater flow based on a dataset of 72 rivers that either directly or indirectly contribute flow to the Arctic Ocean or reflect the hydrologic regime of areas contributing flow to the Arctic Ocean. Annual streamflow for the 72 rivers is categorized as to the nature and location of the contribution to the Arctic Ocean, and composite series of annual flows are determined for each category for the period 1975 to 2015. A trend analysis is then conducted for the annual discharge series assembled for each category. The results reveal a general increase in freshwater flow to the Arctic Ocean with this increase being more prominent from the Eurasian rivers than from the North American rivers. A comparison with trends obtained from an earlier study ending in 2000 indicates similar trend response from the Eurasian rivers, but dramatic differences from some of the North American rivers. A total annual discharge increase of 8.7 km 3 /y/y is found, with an annual discharge increase of 5.8 km 3 /y/y observed for the rivers directly flowing to the Arctic Ocean. The influence of annual or seasonal climate oscillation indices on annual discharge series is also assessed. Several river categories are found to have significant correlations with the Arctic Oscillation, the North Atlantic Oscillation, or the Pacific Decadal Oscillation. However, no significant association with climate indices is found for the river categories leading to the largest freshwater contribution to the Arctic Ocean.

Strategies for integrating water management and spatial planning: Organising for spatial quality in the Dutch “Room for the River” program - Busscher, T.; Van Den Brink, M.; Verweij, S. (Journal of Flood Risk Management, 2019)
In response to extreme flood events and an increasing awareness that traditional flood control measures alone are inadequate to deal with growing flood risks, spatial flood risk management strategies have been introduced. These strategies do not only aim to reduce the probability and consequences of floods, they also aim to improve local and regional spatial qualities. To date, however, research has been largely ignorant as to how spatial quality, as part of spatial flood risk management strategies, can be successfully achieved in practice. Therefore, this research aims to illuminate how spatial quality is achieved in planning practice. This is done by evaluating the configurations of policy instruments that have been applied in the Dutch Room for the River policy program to successfully achieve spatial quality. This policy program is well known for its dual objective of accommodating higher flood levels as well as improving the spatial quality of the riverine areas. Based on a qualitative comparative analysis, we identified three successful configurations of policy instruments. These constitute three distinct management strategies: the “program‐as‐guardian”, the “project‐as‐driver,” and “going all‐in” strategies. These strategies provide important leads in furthering the development and implementation of spatial flood risk management, both in the Netherlands and abroad.
Keywords: Ouvrage_Collectif_Numéro1

A systematic review of school‐based interventions and their outcomes for youth exposed to traumatic events - Yohannan, Justina; Carlson, John S. (Psychology in the Schools, 2019)
Abstract Youth exposed to traumatic events are at higher risk for negative developmental outcomes, including low academic performance, poor social skills, and mental health concerns. To best address these risks, school‐based intervention services, and trauma‐informed practices can be provided. The goal of this study was to systematically review the intervention research conducted on school‐based trauma interventions, with specific attention to examine intervention effectiveness, feasibility, and acceptability across studies. It was found that feasibility and acceptability are not frequently examined, though the data available showed that Enhancing Resiliency Amongst Students Experiencing‐Stress (ERASE‐Stress) and school‐based cognitive behavioral therapy (CBT) had high rates of fidelity; and school‐based CBT had high levels of acceptability. The review also examined demographic variables and found that U. S.‐based research reported racially/ethnically diverse samples, and most samples were from low‐income populations. Most studies examined youth exposed to war‐ and terror‐related traumas or natural disaster‐related traumas. Additionally, this review provides future directions for research and reveals the need for further research on intervention feasibility and acceptability. A brief description of practice recommendations based on prior research has also been included. It also exposes the need for studies that examine various student demographic variables that are currently not examined and consistency in rating scale use in school‐based trauma intervention research.
Keywords: Ouvrage_Collectif_Numéro1

Adaptive meshing methodology based on topometric data for dambreak inundation assessments - Moslemi, Mahdi (École de technologie supérieure, 2019)
Flood maps are the final products of dam failure studies that are required by dam safety regulations. A flood limit, which represents the maximum envelope reached by flood waves, is generally the result of a dam-break scenario simulated by a hydraulic numerical model. However, the numerical model uses only a limited portion of the available bathymetry data to build the terrain model (2D mesh plus topometric elevation at nodes). This is particularly so in the cases where the topo-metric data recorded by LIDAR was estimated in several million points. But the hydraulic numerical models rarely exceed hundreds of thousands of nodes, in particular because of the computer constraints and time associated with the operation of these models. The production of the final flood map requires consistency between projected levels and elevations for all points on the map. This verification may be tedious for a large area with several small secondary valleys of tributary streams that have not been represented by the original hydraulic numerical model. The aim of this work is to propose an automatic remeshing strategy that uses the envelope of the maximum dimensions reached by the original model coupled with the available LIDAR data to produce an improved mesh that can accurately capture the wet/dry fronts and the overflows of the secondary valleys. This model helps us to consider the maximum slope inside each element on the basis of the real data, instead of controlling the slope for not having negative depth or controlling the velocity. The algorithm is based on a few basic steps: (i) find the elements cut by the envelope of the wet/dry interfaces; (ii) project the topometric points onto the cut elements; (iii) if these points are very close to the interface, if they are found in a valley, or if they are more elevated than the corresponding cut elements, then these points will be added to the previous nodes and included in a subsequent triangulation step; and (iv) re-run the simulation on the new mesh. This algorithm has been implemented and validated in the study of a dambreak flow with a complex river topography on the Eastmain River and the Romaine-Puyjalon River.

Caractériser et évaluer la capacité d'adaptation des communautés face aux risques naturels : le cas de Saint-Raymond - Hume, Jonathan (2019)
Les changements climatiques impactent de plus en plus la vie, le développement et la vulnérabilité de plusieurs communautés à travers le monde, lesquelles devant de plus en plus mitiger les risques naturels. Au Québec, la gestion des risques présente une philosophie de « retour à la normale » qui se penche davantage sur les dimensions d’intervention et de rétablissement. Cependant, à la lumière des incertitudes amenées par les changements climatiques, il est impératif que les communautés québécoises aient les capacités d’augmenter leur résilience face aux risques naturels qui s’accentuent rapidement. Ainsi, la capacité d’adaptation doit se retrouver au cœur de la gestion des risques. Cela dit, il existe peu d’outils d’évaluation de la capacité d’adaptation au Québec, entendue comme l’ensemble des ressources dynamiques disponibles et accessibles qui permettent une augmentation de la résilience et une diminution de la vulnérabilité en transformant positivement une communauté et son environnement. La présente recherche vise ainsi à développer une méthode d’analyse de la capacité d’adaptation des individus et des communautés québécoises touchées par les inondations à l’aide de systèmes d’information géographique (SIG), en utilisant la Ville de Saint-Raymond de Portneuf comme étude de cas. Ce projet se base principalement sur les concepts de vulnérabilité, de résilience et d’adaptation pour recenser des indicateurs pouvant servir à caractériser et évaluer la capacité des personnes et municipalités exposées aux inondations à mobiliser les ressources nécessaires pour non seulement atténuer les risques lors de tels événements, mais aussi mieux les prévenir et s’en préparer. Des données socioéconomiques et d’aménagement du territoire sont notamment mises à profit pour des fins d’analyse de même que des données issues d’un sondage effectué en 2014 à la suite d’une inondation majeure par la CAPSA, l’organisme de bassin versant de la région de Portneuf, en collaboration avec le comité Rivière de la Ville de Saint-Raymond.

Groundwater Buffers Decreasing Glacier Melt in an Andean Watershed—But Not Forever - Somers, Lauren D.; McKenzie, Jeffrey M.; Mark, Bryan G.; Lagos, Pablo; Ng, Gene‐Hua Crystal; Wickert, Andrew D.; Yarleque, Christian; Baraër, Michel; Silva, Yamina (Geophysical Research Letters, 2019)
Abstract Accelerating mountain glacier recession in a warming climate threatens the sustainability of mountain water resources. The extent to which groundwater will provide resilience to these water resources is unknown, in part due to a lack of data and poorly understood interactions between groundwater and surface water. Here we address this knowledge gap by linking climate, glaciers, surface water, and groundwater into an integrated model of the Shullcas Watershed, Peru, in the tropical Andes, the region experiencing the most rapid mountain‐glacier retreat on Earth. For a range of climate scenarios, our model projects that glaciers will disappear by 2100. The loss of glacial meltwater will be buffered by relatively consistent groundwater discharge, which only receives minor recharge (~2%) from glacier melt. However, increasing temperature and associated evapotranspiration, alongside potential decreases in precipitation, will decrease groundwater recharge and streamflow, particularly for the RCP 8.5 emission scenario. , Plain Language Summary Mountain regions play an important role in water supply, because meltwater from snow and ice feeds rivers during dry periods. Groundwater (water stored in the pore spaces of soils and rock), which flows into rivers, is also an important store of water in mountain areas and may help to protect water resources against the negative impacts of shrinking mountain glaciers. We used extensive field measurements and computer modeling of the Shullcas Watershed in the Peruvian Andes to determine the current and future role of groundwater in the face of climate change. Our model projects that glaciers in our study area will disappear by 2100. The loss of glacier meltwater is buffered in the short term (~30 years) by consistent groundwater flow to rivers. However, in the long term (>60 years), precipitation is expected to decrease and rising temperatures lead to increased evaporation and water use by plants. These factors reduce groundwater recharge and storage, causing dry season streamflow to drop. , Key Points Groundwater accounts for a large fraction of streamflow and only receives minor (~2%) recharge from glaciers in the study catchment in Peru As meltwater decreases, groundwater provides consistent discharge in the near term (~30 years), becoming a larger fraction of streamflow In the long term (>60 years), groundwater storage and discharge decrease in response to higher evapotranspiration and lower precipitation
Keywords: Baraer_Michel

Potential for Sugar Maple to Provide High-Quality Sawlog Trees at the Northern Edge of Its Range - Guillemette, François; Bédard, Steve (Forest Science, 2019)
Abstract The management of sugar maple (Acer saccharum) at the northern edge of its range is mainly oriented toward timber production, from trees of higher grades. However, both the quality of mature trees in natural stands and how the quality may vary depending on the silvicultural treatment are unknown, especially under northern conditions. The objective of this study was to describe the variation in stem quality of mature maple trees (diameter >33 cm) according to climatic, geographic or soil variables, and to evaluate the effects of a first selection cutting cycle on this quality. Annual temperature (1.7–4.1° C) was the most important variable explaining differences in the proportion of higher-grade trees, with a 16 percent gain associated with every additional increase in degrees Celsius. The practice of a first selection cutting was associated with an 11 percent gain in this proportion. Although the actual proportion of high-quality trees was below 35 percent on the coolest sites, a proper tree selection through silviculture could likely improve this proportion in future decades, whereas the potential effects of climate change are unclear.
Keywords: Guillemette_Francois

More food with less water – Optimizing agricultural water use - Smilovic, Mikhail; Gleeson, Tom; Adamowski, Jan; Langhorn, Colin (Advances in Water Resources, 2019)

Effets à long terme de la thérapie cognitive-comportementale pour le trouble de stress post-traumatique - Flores, Thalie; Gaboury, Marie-Pier; Fiset, Noémie; Boily, Leslie-Ann; Belleville, Geneviève (Psycause : revue scientifique étudiante de l'École de psychologie de l'Université Laval, 2019)
La thérapie cognitive-comportementale (TCC) pour le trouble de stress post-traumatique (TSPT) est validée empiriquement (Forman-Hoffman et al., 2018). Toutefois, à notre connaissance, aucune revue de la littérature ne s’intéresse précisément à l’efficacité à long terme de la TCC du TSPT. Il importe pourtant de s’assurer avec une vision d’ensemble de la durabilité des gains thérapeutiques afin de vérifier si la TCC du TSPT permet d’éviter un retour des symptômes après la thérapie. Des études ont observé que les gains thérapeutiques se maintiendraient entre 6 et 20 mois après la TCC (voir, p. ex., Hembree & Foa, 2000; Kline, Cooper, Rytwinksi, & Feeny, 2018) et qu’ils pourraient même s’améliorer (Hembree & Foa, 2000). La présente revue de littérature identifie des études de traitement, des revues de littérature et des méta-analyses abordant l’efficacité à long terme d’une TCC du TSPT. Ce projet répertorie également les facteurs influençant l’efficacité à long terme d’une TCC individuelle, de groupe et par vidéoconférence. Des articles publiés entre 2010 et 2018 ont été cherchés dans les bases de données MEDLINE et PsycINFO. Deux constats se dégagent de cette revue, soit que la TCC permettrait de traiter le TSPT de façon durable et que certaines variables comme la dépression ou l’anxiété comorbide, un âge avancé, des difficultés de sommeil persistantes et le fait de tarder à aller chercher de l’aide sont associées à une moins bonne efficacité à long terme de la TCC du TSPT. Il est possible que le développement d’habiletés d’adaptation en thérapie soit un facteur de maintien et même d’amélioration des gains après la TCC.
Keywords: Site_internet_RIISQ

Using the Mann–Kendall test and double mass curve method to explore stream flow changes in response to climate and human activities - Pirnia, Abdollah; Golshan, Mohammad; Darabi, Hamid; Adamowski, Jan; Rozbeh, Sajad (Journal of Water and Climate Change, 2019)
Abstract Analyzing intra-annual stream flow can reveal the main causes for runoff changes and the contributions of climate variability and human activities. For this purpose, the Mann–Kendall and cumulative rank difference (CRD) tests, and the double mass curve method, were applied to a time series of hydro-meteorological variables from 1971 to 2010 in the Tajan River basin in Iran. Results indicated that runoff changes in the wet and dry seasons after 1999 had significant respective decreasing and increasing trends, at the 0.01 confidence level, due to dam construction. In the pre-dam period (1991–1998), the results of the double mass curve method showed that climate variability and human activities contributed 57.76% and 42.24%, respectively, to the runoff decrease during the wet season. For the post-dam period (1999–2010), climate variability and anthropogenic activities contributed 24.68% and 75.32%, respectively, to the wet season runoff decrease of 116.55 mm. On the other hand, in the same period during the dry season, climate variability contributed −30.68% and human activities contributed 130.68% to the runoff increase of 41.45 mm. It is evident that runoff changes in both wet and dry seasons were mainly due to human activities associated with dam construction to meet water supply demands for agriculture.

Global Meta‐Analysis on the Relationship Between Mercury and Dissolved Organic Carbon in Freshwater Environments - Lavoie, Raphael A.; Amyot, Marc; Lapierre, Jean‐François (Journal of Geophysical Research: Biogeosciences, 2019)
Abstract In freshwater ecosystems, several studies have shown a strong linear relationship between total mercury (THg) or methylmercury (MeHg) and dissolved organic carbon (DOC) concentrations. Variations in this linear relationship have been reported, but the magnitude and causes of this variation are not well known. The objective of this study was to conduct a meta‐analysis to quantify and understand the global variation of this mercury (Hg)–DOC association. This meta‐analysis included 54 studies in lentic and lotic ecosystems for a total of 85 THg–DOC and 59 MeHg–DOC relationships. There was an increase in Hg with DOC concentrations in water with a global average slope of 0.25 (confidence interval (CI): 0.20–0.35) ng/mg for THg and 0.029 (CI: 0.014–0.044) ng/mg for MeHg. Relationships were stronger for (1) North American studies, (2) natural environments compared to those disturbed by anthropogenic activities, (3) spatial studies compared to temporal studies, (4) filtered samples (THg only), and (5) the aromatic fraction of DOC compared to the bulk DOC. Coupling with DOC was stronger for THg than for MeHg. Ecosystem type (lentic vs. lotic), geographical coordinates, and publication year did not influence the strength of relationships. Overall, we show that there is a strong but variable coupling between carbon and mercury cycles in freshwater ecosystems globally and that this link is modulated regionally by geographic location, temporal scale, and human activity, with implications for understanding these rapidly changing biogeochemical processes in response to global change. , Plain Language Summary In lakes and rivers, organic carbon is known to be a transporter of mercury, a toxic metal. However, depending on the chemistry of waterbodies, carbon can carry different amounts of mercury. This work compiled results of 54 scientific studies around the world looking at the correlation between mercury and organic carbon. We looked at the conditions that make this relationship vary. We found that relationships were almost always positive and that the type of carbon influenced the amount of mercury that was carried. The strength of those relationships was higher in natural ecosystems compared to those with human influence and in North American ecosystems compared to European and Asian ones. This work is important to understand the mechanism behind the association between mercury and carbon in different environments and how carbon can be used to explain variations in mercury, especially in a changing climate under human pressure. , Key Points Mercury and dissolved organic matter coupling is stronger in spatial studies, in North America, in natural systems, and in filtered samples Correlations are stronger with the aromatic fraction than the bulk dissolved organic carbon and stronger for total than methyl mercury Ecosystem type (lentic vs. lotic), geographical coordinates, and publication year had no effect on the strength of relationships

Differing Modes of Biotic Connectivity within Freshwater Ecosystem Mosaics - Mushet, David M.; Alexander, Laurie C.; Bennett, Micah; Schofield, Kate; Christensen, Jay R.; Ali, Genevieve; Pollard, Amina; Fritz, Ken; Lang, Megan W. (JAWRA Journal of the American Water Resources Association, 2019)
Abstract We describe a collection of aquatic and wetland habitats in an inland landscape, and their occurrence within a terrestrial matrix, as a “freshwater ecosystem mosaic” (FEM). Aquatic and wetland habitats in any FEM can vary widely, from permanently ponded lakes, to ephemerally ponded wetlands, to groundwater‐fed springs, to flowing rivers and streams. The terrestrial matrix can also vary, including in its influence on flows of energy, materials, and organisms among ecosystems. Biota occurring in a specific region are adapted to the unique opportunities and challenges presented by spatial and temporal patterns of habitat types inherent to each FEM. To persist in any given landscape, most species move to recolonize habitats and maintain mixtures of genetic materials. Species also connect habitats through time if they possess needed morphological, physiological, or behavioral traits to persist in a habitat through periods of unfavorable environmental conditions. By examining key spatial and temporal patterns underlying FEMs, and species‐specific adaptations to these patterns, a better understanding of the structural and functional connectivity of a landscape can be obtained. Fully including aquatic, wetland, and terrestrial habitats in FEMs facilitates adoption of the next generation of individual‐based models that integrate the principles of population, community, and ecosystem ecology. , Research Impact Statement : Fully including aquatic, wetland, and terrestrial habitats facilitates adoption of next‐generation, individual‐based, models that integrate principles of population, community, and ecosystem ecology.

Le Québec récemment frappé par les crues extrêmes : une manifestation des changements climatiques ? - Leconte, Robert (Le Climatoscope, 2019)
Les printemps 2017 et 2019 auront frappé l’imaginaire collectif en raison de l’ampleur des crues ayant touché de nombreuses rivières du Québec et des dommages qui leur sont associés. En 2019, près de 6700 résidences localisées dans 51 municipalités et distribuées dans presque toutes les principales régions du Québec ont été inondées, sans compter les nombreuses autres résidences qui se sont retrouvées isolées en raison de routes submergées et de glissements de terrain. Le bilan en 2017 était similaire, avec 5371 maisons inondées dans 261 municipalités et 4066 personnes évacuées. Les débits dans plusieurs rivières ont excédé les valeurs mesurées depuis que les stations de jaugeage ont été installées. À titre d’exemple, en 2019, le débit journalier dans la rivière Rouge à la hauteur du Barrage de la Chute-Bell, où Hydro-Québec a craint pour la stabilité de l’ouvrage, a atteint 975 m3/s, la plus forte valeur jamais enregistrée depuis 1964. Une analyse statistique révèle qu’un tel débit a une chance d’être dépassé en moyenne une fois tous les 175 ans. Il s’agit d’un événement exceptionnel. Pourtant, un autre événement extrême se produisait au même endroit en 1998, cette fois-ci avec un débit maximal journalier de 914 m3/s. Deux crues printanières majeures en 20 ans : est-ce la conséquence des changements climatiques ? Cet article propose une genèse des événements hydrologiques extrêmes, puis présente des projections climatiques aux horizons 2050 et 2080 pour différentes rivières au Sud et au Nord du fleuve Saint-Laurent. Puis, est exposée la démarche générale employée pour caractériser le régime hydrologique des bassins versants en climat futur.
Keywords: Ouvrage_Collectif_Numéro1

Quarante ans de participation publique en environnement, aménagement du territoire et urbanisme au Québec : entre expression des conflits et gestion consensuelle - Bherer, Laurence; Gauthier, Mario; Simard, Louis (Cahiers de géographie du Québec, 2019)
En près de 40 ans, les revendications pour plus de participation et de transparence, ainsi que la diffusion du principe de développement durable ont profondément transformé les secteurs de l’environnement, de l’aménagement du territoire et de l’urbanisme. Au fil des décennies, divers types de dispositifs de participation publique ont vu le jour dans ces deux secteurs d’activité qui ont permis de démocratiser le rapport gouvernants / gouvernés et la relation entre les pouvoirs publics et la société civile. À partir d’une grille d’analyse axée sur deux dimensions – ouverture / fermeture et antagoniste / consensuel – nous analysons les différents dispositifs de participation publique à l’oeuvre dans ces deux secteurs. L’analyse tend à montrer que : 1) au cours des 40 dernières années, les dispositifs participatifs se sont multipliés ; 2) aux dispositifs participatifs traditionnels permettant l’expression des conflits et des oppositions se sont progressivement ajoutés des dispositifs davantage orientés vers la recherche du consensus et la résolution des conflits ; 3) de nos jours, ces deux grandes catégories de dispositifs cohabitent et peuvent parfois apparaître comme étant complémentaires et parfois comme étant contradictoires. , Over the past 40 years, demands for greater participation, transparency and the dissemination of the principle of sustainable development have transformed the areas of environment, land-use planning and urban planning. Over the decades, various types of public participation mechanisms have emerged in these sectors that helped democratize the rulers / governed report and the relationship between public authorities and civil society. Starting from a grid analysis based on two dimensions—opening / closing and antagonist / consensus—this article analyses the different public participation mechanisms at work in these two areas. Analysis tends to demonstrate that during the last forty years the number of participatory mechanisms has increased. Moreover, devices oriented towards the search for consensus and conflict resolution were gradually added to the traditional participatory mechanisms that allowed for the voicing of concerns and oppositions. Currently, these two broad categories of participatory tools coexist and can at times appear complementary and at others contradictory. , En casi cuarenta años, las reivindicaciones de mayor participación y transparencia, tanto como la difusión del principio de desarrollo sostenido, han transformado profundamente los sectores del medio ambiente, de la planificación territorial y del urbanismo. Con el correr de las décadas, varios tipos de dispositivos de participación pública surgieron en esos dos sectores de actividad que permitieron democratizar la relación gobernantes / gobernados y la relación poderes públicos y la sociedad civil. Gracias a una tabla de análisis con dos coordenadas – apertura / cierre y antagonista / consensual – analizamos diferentes dispositivos de participación pública que actúan en esos dos sectores. El análisis propone que: 1) durante los últimos cuarenta años, los dispositivos de participación han aumentado. 2) A los dispositivos participativos tradicionales que permiten la expresión de conflictos y oposiciones, se añadieron progresivamente dispositivos mejor orientados hacia la busqueda de consenso y de solución de conflictos. 3) Hoy, esas dos grandes categorías de dispositivos cohabitan y hasta parecen unas veces complementarias y otras contradictorias.
Keywords: Ouvrage_Collectif_Numéro1

Impact of Soil Moisture Data Characteristics on the Sensitivity to Crop Yields Under Drought and Excess Moisture Conditions - Champagne, Catherine; White, Jenelle; Berg, Aaron A.; Bélair, Stéphane; Carrera, Marco L. (Remote Sensing, 2019)
Soil moisture is often considered a direct way of quantifying agricultural drought since it is a measure of the availability of water to support crop growth. Measurements of soil moisture at regional scales have traditionally been sparse, but advances in land surface modelling and the development of satellite technology to indirectly measure surface soil moisture has led to the emergence of a number of national and global soil moisture data sets that can provide insight into the dynamics of agricultural drought. Droughts are often defined by normal conditions for a given time and place; as a result, data sets used to quantify drought need a representative baseline of conditions in order to accurately establish a normal. This presents a challenge when working with earth observation data sets which often have very short baselines for a single instrument. This study assessed three soil moisture data sets: a surface satellite soil moisture data set from the Soil Moisture and Ocean Salinity (SMOS) mission operating since 2010; a blended surface satellite soil moisture data set from the European Space Agency Climate Change Initiative (ESA-CCI) that has a long history and a surface and root zone soil moisture data set from the Canadian Meteorology Centre (CMC)’s Regional Deterministic Prediction System (RDPS). An iterative chi-squared statistical routine was used to evaluate each data set’s sensitivity to canola yields in Saskatchewan, Canada. The surface soil moisture from all three data sets showed a similar temporal trend related to crop yields, showing a negative impact on canola yields when soil moisture exceeded a threshold in May and June. The strength and timing of this relationship varied with the accuracy and statistical properties of the data set, with the SMOS data set showing the strongest relationship (peak X2 = 170 for Day of Year 145), followed by the ESA-CCI (peak X2 = 89 on Day of Year 129) and then the RDPS (peak X2 = 65 on Day of Year 129). Using short baseline soil moisture data sets can produce consistent results compared to using a longer data set, but the characteristics of the years used for the baseline are important. Soil moisture baselines of 18–20 years or more are needed to reliably estimate the relationship between high soil moisture and high yielding years. For the relationship between low soil moisture and low yielding years, a shorter baseline can be used, with reliable results obtained when 10–15 years of data are available, but with reasonably consistent results obtained with as few as 7 years of data. This suggests that the negative impacts of drought on agriculture may be reliably estimated with a relatively short baseline of data.
MAG ID: 2912601201

Spatialisation des processus d’embâcles dans le bassin versant de la rivière l’Acadie, Montérégie : une approche hydrogéomorphologique - Plante Lévesque, Valérie; Boucher, Étienne; Proulx, Guillaume (Revue des sciences de l’eau, 2019)
La rivière L’Acadie, située en Montérégie (Québec, Canada), est un affluent de la rivière Richelieu et s’écoule vers le nord. Des inondations hivernales ayant de lourds impacts sur les milieux habités des municipalités de Chambly et de Carignan sont fréquentes sur cette rivière. Alors qu’au Québec on privilégie une approche hydrologique basée sur la récurrence des inondations en eau libre pour aménager les rives et la plaine inondable, l’approche hydrogéomorphologique permet de spatialiser les processus fluviaux qui posent un risque pour les communautés à partir d’une étude détaillée et systématique des formes du paysage fluvial. Cette approche permet d’acquérir une meilleure idée de l’impact de certains processus fluviaux tels que les embâcles de glace sur l’environnement humain et naturel. La présente recherche a pour objectif de spatialiser les propriétés et les impacts géomorphologiques du régime d’embâcles de glace au sein du bassin versant de la rivière L’Acadie. Des caractérisations des propriétés du bassin versant, du chenal, puis des berges de la rivière sont effectuées afin de localiser les problèmes d’embâcles de glace et décrire l’intensité de leur empreinte morphologique sur le milieu. De ces résultats découle une typologie des berges à laquelle est jumelée une analyse de la fréquence des évènements par l’étude des cicatrices glacielles sur la végétation riveraine. L’analyse démontre comment la morphométrie du chenal, la présence d’agriculture ainsi que l’héritage de la dernière glaciation quaternaire affectent le dynamisme du régime d’embâcles de glace qui se concentre en aval de la rivière. , L’Acadie River is a tributary of the Richelieu River that flows northwards through the southwestern region of Montérégie (Quebec, Canada). The river is well known for its frequent winter floods that severely affect the nearby towns of Chambly and Carignan. Even though legislation in Quebec has an approach based on the frequency of open water floods to control riverbanks and floodplain development, the study of river forms, known as hydrogeomorphology, provides a more comprehensive understanding of the impact of fluvial processes such as river ice jams. The main objective of this research is to gain knowledge on river ice dynamics based on their spatialization within L’Acadie River watershed. The characterization of the watershed, channel, and river bank properties and features is based on a hydrogeomorphological approach to spatialize river ice activity along the river. The study emphasizes that watershed properties, the ubiquity of agriculture, and the legacy of the Quaternary ice period in the area are all factors that contribute to ice scouring activity in the downstream section of the main channel.
Keywords: Ouvrage_Collectif_Numéro1

Medicaid Utilization Before and After a Natural Disaster in the 2016 Baton Rouge–Area Flood - Phillippi, Stephen W.; Beiter, Kaylin; Thomas, Casey L.; Sugarman, Olivia K.; Wennerstrom, Ashley; Wells, Kenneth B.; Trapido, Edward (American Journal of Public Health, 2019)
Objectives. To understand changes in behavioral health services utilization and expenditures before and after natural disaster with an adult Medicaid population affected by the Baton Rouge, Louisiana–area flood (August 2016). Methods. We examined de-identified behavioral health claims data for Medicaid-insured adults in the affected region for 10 months before and after flooding (October 2015–June 2017). This constituted 273 233 provider claims for 22 196 individuals. Claims data included patient gender, behavioral health diagnoses, treatment dates, and costs. We made adjustments for Medicaid expansion by using monthly enrollment data. Results. Overall, most male patient behavioral health care visits were for substance use disorders (33.6%) and most female patient behavioral health care visits were for depression-related disorders (30%). Both diagnostic categories increased after the flood by 66% and 44%, respectively. Expansion accounted for a 4% increase in claims. Postflood claims reflected 8% to 10% higher costs. Conclusions. Greater amounts of behavioral health care services were sought in all 10 months of the postflood study period. We observed gender differences in use of services and diagnoses. Behavioral health care services following natural disasters must be extended longer than traditionally expected, with consideration for specific population needs.
Keywords: Ouvrage_Collectif_Numéro1

Are We Adapting to Floods? Evidence from Global Flooding Fatalities - Miao, Qing (Risk Analysis, 2019)
Abstract There has been a growing interest in understanding whether and how people adapt to extreme weather events in a changing climate. This article presents one of the first empirical analyses of adaptation to flooding on a global scale. Using a sample of 97 countries between 1985 and 2010, we investigate the extent and pattern of flood adaptation by estimating the effects of a country's climatological risk, recent flood experiences, and socioeconomic characteristics on its flood‐related fatalities. Our results provide mixed evidence on adaptation: countries facing greater long‐term climatological flooding risks do not necessarily adapt better and suffer fewer fatalities; however, after controlling for the cross‐country heterogeneity, we find that more recent flooding shocks have a significant and negative effect on fatalities from subsequent floods. These findings may suggest the short‐term learning dynamics of adaptation and potential inefficacy of earlier flood control measures, particularly those that promote increased exposure in floodplains. Our findings provide important implications for climate adaptation policy making and climate modeling.

Long-term consequences of flooding: a case study of the 2011 Queensland floods - Fitzgerald, Gerard; Toloo Sheikhzadeh Yazd, Sam; Baniahmadi, Sara; Crompton, David; Tong, Shilu (Australian Journal of Emergency Management, 2019)
Devastating floods in southeast Queensland in 2011 were the combination of flash flooding in the Lockyer Valley with riverine flooding in the Brisbane metropolitan area. While there is considerable information about the immediate impact on those affected, there is less understanding of the long-term health effects that follow such events. This study explored the perceptions of health effects and support received by people affected by the 2011 southeast Queensland flood six years after the event. A cross-sectional survey of 327 people was conducted in areas affected by the floods. The questionnaire sought information about the ongoing social, economic, demographic and self-declared physical and mental health effects. The data were analysed through comparison of those unaffected with those directly affected by the floods. Residents whose households were flooded were more likely to score their health negatively than non-affected residents and had higher reported rates of trauma, injury and mental illness. Twenty-six per cent of this group reported that they still experience some adverse health effects from the floods. Managing the long-term health implications of a flood-affected population is an important public policy task. Dissatisfaction with recovery operations and perceived injustices associated with insurance and compensation arrangements may aggravate health consequences. Early recognition and intervention may assist with reducing secondary effects.
Number: 1 Publisher: Emergency Management Australia
Keywords: Ouvrage_Collectif_Numéro1

Flooding Related Consequences of Climate Change on Canadian Cities and Flow Regulation Infrastructure - Gaur, Ayushi; Gaur, Abhishek; Yamazaki, Dai; Simonovic, Slobodan P. (Water, 2019)
This study discusses the flooding related consequences of climate change on most populous Canadian cities and flow regulation infrastructure (FRI). The discussion is based on the aggregated results of historical and projected future flooding frequencies and flood timing as generated by Canada-wide hydrodynamic modelling in a previous study. Impact assessment on 100 most populous Canadian cities indicate that future flooding frequencies in some of the most populous cities such as Toronto and Montreal can be expected to increase from 100 (250) years to 15 (22) years by the end of the 21st century making these cities highest at risk to projected changes in flooding frequencies as a consequence of climate change. Overall 40–60% of the analyzed cities are found to be associated with future increases in flooding frequencies and associated increases in flood hazard and flood risk. The flooding related impacts of climate change on 1072 FRIs located across Canada are assessed both in terms of projected changes in future flooding frequencies and changes in flood timings. Results suggest that 40–50% of the FRIs especially those located in southern Ontario, western coastal regions, and northern regions of Canada can be expected to experience future increases in flooding frequencies. FRIs located in many of these regions are also projected to experience future changes in flood timing underlining that operating rules for those FRIs may need to be reassessed to make them resilient to changing climate.
MAG ID: 2908236810

Exploring the Environmental Justice Implications of Hurricane Harvey Flooding in Greater Houston, Texas. - Chakraborty, Jayajit; Collins, Timothy W.; Grineski, Sara E. (American Journal of Public Health, 2019)
Objectives. To assess the environmental justice implications of flooding from Hurricane Harvey in Greater Houston, Texas, we analyzed whether the areal extent of flooding was distributed inequitably with respect to race, ethnicity, and socioeconomic status, after controlling for relevant explanatory factors.Methods. Our study integrated cartographic information from Harvey’s Inundation Footprint, developed by the US Federal Emergency Management Agency, with sociodemographic data from the 2012–2016 American Community Survey. Statistical analyses were based on bivariate correlations and multivariate generalized estimating equations.Results. The areal extent of Harvey-induced flooding was significantly greater in neighborhoods with a higher proportion of non-Hispanic Black and socioeconomically deprived residents after we controlled for contextual factors and clustering.Conclusions. Results provide evidence of racial/ethnic and socioeconomic injustices in the distribution of flooding and represent an importa...
MAG ID: 2906468836

La portée et les limites des approches participatives pour la gestion intégrée des inondations - Massé, Simon; Buffin-Bélanger, Thomas; Biron, Pascale; Ruiz, Julie (Revue des sciences de l’eau, 2019)
La gestion intégrée des risques d’inondation (GIRI) fait appel à la coordination de tous les niveaux et secteurs du gouvernement et de la société civile. Afin de favoriser la responsabilisation et l’appropriation des plans de GIRI par les communautés, l’implication des acteurs non gouvernementaux et des citoyens est de plus en plus valorisée. D’abord, l’émergence des approches participatives est exacerbée par l’optimisme face à la possibilité d’améliorer substantiellement la qualité et la portée des décisions, de gérer les conflits, de faciliter l'implantation des mesures non structurelles et de renforcer les capacités sociales au sein des communautés. Toutefois, certains avancent que l'intégration des non-experts dans le processus décisionnel brime l'impartialité de la procédure technocratique et que leur manque d’intérêt et de compétences limite la portée des démarches participatives. Des lacunes dans la représentativité des parties prenantes affectées et concernées au sein des instances peuvent aussi biaiser les aboutissants de la participation. De plus, la réticence des autorités à partager le pouvoir décisionnel limite l’institutionnalisation des approches participatives, tandis que la rigidité de l’appareil gouvernemental freine les élans participatifs des collectivités. Considérant l’intérêt grandissant des chercheurs, des décideurs et de la société civile envers les approches participatives dans le contexte de la gestion des inondations, cet article propose une synthèse de la littérature pour démêler les principales retombées et les limites de la participation. , In order to promote community accountability for flood risks, the involvement of non-governmental actors and citizens is increasingly valued. The emergence of participatory approaches is consolidated by optimism about the possibility of improving the quality and scope of decisions, managing conflicts, facilitating the implementation of non-structural measures and strengthening social capacity within communities. However, some argue that the integration of non-experts undermines the impartiality of the decision-making process and that their lack of interest and expertise limits the scope of participatory approaches. Moreover, the authorities’ reluctance to share decision-making power limits the institutionalization of participatory approaches, whereas the rigidity of the governmental framework hampers participatory impulses within communities. Lack of stakeholder representativeness within the decision-making framework may also bias the outcome of participation. In addition, the reluctance of the authorities to share decision-making power limits the institutionalization of participatory approaches, while the rigidity of the government apparatus hinders the participatory momentum of communities. Considering the growing interest of researchers, policymakers and civil society in participatory approaches in the context of flood management, this article provides a synthesis of the literature to unravel the major benefits and limitations of participation.
Keywords: Ouvrage_Collectif_Numéro1

Risk assessment strategies for early detection and prediction of infectious disease outbreaks associated with climate change - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Canada Communicable Disease Report, 2019)
Keywords: Gachon_Philippe

Stratégie d’évaluation des risques servant à la détection précoce et à la prédiction des éclosions de maladies infectieuses associées aux changements climatiques - Rees, Ee; Ng, V; Gachon, P; Mawudeku, A; McKenney, D; Pedlar, J; Yemshanov, D; Parmely, J; Knox, J (Relevé des maladies transmissibles au Canada, 2019)
Keywords: Gachon_Philippe

The role of place meanings in opposition to water-related infrastructure projects: the case of the Mactaquac Dam, New Brunswick, Canada - Reilly, Kate H.; Adamowski, Jan F.; John, Kimberly (Ecology and Society, 2019)

Modelling the impacts of climate change on riverine thermal regimes in western Canada's largest Pacific watershed. - Islam, Siraj ul; Hay, Rachel W.; Déry, Stephen J.; Booth, Barry P. (Scientific Reports, 2019)
Quantification of climate change impacts on the thermal regimes of rivers in British Columbia (BC) is crucial given their importance to aquatic ecosystems. Using the Air2Stream model, we investigate the impact of both air temperature and streamflow changes on river water temperatures from 1950 to 2015 across BC’s 234,000 km2 Fraser River Basin (FRB). Model results show the FRB’s summer water temperatures rose by nearly 1.0°C during 1950–2015 with 0.47°C spread across 17 river sites. For most of these sites, such increases in average summer water temperature have doubled the number of days exceeding 20°C, the water temperature that, if exceeded, potentially increases the physiological stress of salmon during migration. Furthermore, river sites, especially those in the upper and middle FRB, show significant associations between Pacific Ocean teleconnections and regional water temperatures. A multivariate linear regression analysis reveals that air temperature primarily controls simulated water temperatures in the FRB by capturing ~80% of its explained variance with secondary impacts through river discharge. Given such increases in river water temperature, salmon returning to spawn inthe Fraser River and its tributaries are facing continued and increasing physical challenges now and potentially into the future.
MAG ID: 2964716869

Supporting and Accompanying Young People After the Lac-Mégantic Train Derailment (Quebec, Canada) - Généreux, Mélissa; Maillet, Marie-Claude; Nault-Horvath, Elise; Stewart, Cindy (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train transporting oil derailed and exploded in Lac-Mégantic, causing major human, environmental, and economic impacts. A community-based survey of people aged 10-25, conducted in 2017, revealed that many young people suffer in silence and report feeling isolated. These observations led to the conclusion that we must make room for young people, and that opportunities for engagement and participation must be provided within the community.Aim:The Public Health Direction of Estrie aimed to identify strategies to promote health and wellbeing for young people living in and around Lac-Mégantic.Methods:A collective reflection half-day was hosted with sixty key stakeholders (school board, other education institutions, health and social services, community sector, municipal/political sector, parents, youth). Throughout the event, participants were invited to build on and learn from accomplishments and experiential knowledge, and develop a common vision of the solutions to be pursued or implemented. All qualitative data sources (verbal and written data from large- and sub-group activities) were analyzed through a content analysis.Results:Several themes (i.e. potential solutions) emerged from the analysis: common venue, diversified activities, communication, collaboration, involvement, support for at-risk youth, intergenerational component, etc. Participants agreed on four priorities for action: 1) creating a gathering place, 2) establishing a Youth Committee, 3) supporting adults working with youth, and 4) fostering a better flow of information.Discussion:Several positive outcomes of the collective reflection half-day were observed, including the mobilization of the participants who greatly appreciated the event, and many promising ideas launched by stakeholders. A social worker is now fully dedicated to supporting youth wellbeing and engagement in Lac-Mégantic. A Youth Committee has been established and projects by and for youth are being implemented. Bottom-up approaches to identify solutions to complex situations are not only effective but also respectful of the local culture.
Keywords: Généreux_Mélissa

Future realities of climate change impacts: an integrated assessment study of Canada - Akhtar, Mohammad Khaled; Simonovic, Slobodan P.; Wibe, Jacob; MacGee, James (International Journal of Global Warming, 2019)
This paper presents an integrated assessment model for use with climate policy decision making in Canada. The feedback based integrated assessment model ANEMI_CDN represents Canada within the global society-biosphere-climate-economy-energy system. The model uses a system dynamics simulation approach to investigate the impacts of climate change in Canada and policy options for adapting to changing global conditions. The disaggregation techniques allow ANEMI_CDN to show results with various temporal resolutions. Two Canadian policy scenarios are presented as illustrative examples to map policy impacts on key model variables, including population, water-stress, food production, energy consumption, and emissions under changing climate over this century. The main finding is a significant impact of a carbon tax on energy consumption. Two policy scenario simulations provide additional insights to policy makers regarding the choice of adaptation/mitigation options along with their implementation time.
MAG ID: 2900571356

Sensitivity of seasonal flood simulations to regional climate model spatial resolution - Castaneda-Gonzalez, Mariana; Poulin, Annie; Romero-Lopez, Rabindranarth; Arsenault, Richard; Brissette, François; Turcotte, Richard (Climate Dynamics, 2019)
The potential impacts of floods are of significant concern to our modern society raising the need to identify and quantify all the uncertainties that can impact their simulations. Climate simulations at finer spatial resolutions are expected to bring more confidence in these hydrological simulations. However, the impact of the increasing spatial resolutions of climate simulations on floods simulations has to be evaluated. To address this issue, this paper assesses the sensitivity of summer–fall flood simulations to the Canadian Regional Climate Model (CRCM) grid resolution. Three climate simulations issued from the fifth version of the CRCM (CRCM5) driven by the ERA-Interim reanalysis at 0.44°, 0.22° and 0.11° resolutions are analysed at a daily time step for the 1981–2010 period. Raw CRCM5 precipitation and temperature outputs are used as inputs in the simple lumped conceptual hydrological model MOHYSE to simulate streamflows over 50 Quebec (Canada) basins. Summer–fall flooding is analysed by estimating four flood indicators: the 2-year, 5-year, 10-year and 20-year return periods from the CRCM5-driven streamflows. The results show systematic impacts of spatial resolution on CRCM5 outputs and seasonal flood simulations. Floods simulated with coarser climate datasets present smaller peak discharges than those simulated with the finer climate outputs. Smaller catchments show larger sensitivity to spatial resolution as more detail can be obtained from the finer grids. Overall, this work contributes to understanding the sensitivity of streamflow modelling to the climate model’s resolution, highlighting yet another uncertainty source to consider in hydrological climate change impact studies.
MAG ID: 2943504261

Comparative Analysis of High-Resolution Soil Moisture Simulations from the Soil, Vegetation, and Snow (SVS) Land Surface Model Using SAR Imagery Over Bare Soil - Dabboor, Mohammed; Sun, Lili; Sun, Leqiang; Carrera, Marco L.; Friesen, Matthew; Merzouki, Amine; McNairn, Heather; Powers, Jarrett; Bélair, Stéphane (Water, 2019)
Soil moisture is a key variable in Earth systems, controlling the exchange of water and energy between land and atmosphere. Thus, understanding its spatiotemporal distribution and variability is important. Environment and Climate Change Canada (ECCC) has developed a new land surface parameterization, named the Soil, Vegetation, and Snow (SVS) scheme. The SVS land surface scheme features sophisticated parameterizations of hydrological processes, including water transport through the soil. It has been shown to provide more accurate simulations of the temporal and spatial distribution of soil moisture compared to the current operational land surface scheme. Simulation of high resolution soil moisture at the field scale remains a challenge. In this study, we simulate soil moisture maps at a spatial resolution of 100 m using the SVS land surface scheme over an experimental site located in Manitoba, Canada. Hourly high resolution soil moisture maps were produced between May and November 2015. Simulated soil moisture values were compared with estimated soil moisture values using a hybrid retrieval algorithm developed at Agriculture and Agri-Food Canada (AAFC) for soil moisture estimation using RADARSAT-2 Synthetic Aperture Radar (SAR) imagery. Statistical analysis of the results showed an overall promising performance of the SVS land surface scheme in simulating soil moisture values at high resolution scale. Investigation of the SVS output was conducted both independently of the soil texture, and as a function of the soil texture. The SVS model tends to perform slightly better over coarser textured soils (sandy loam, fine sand) than finer textured soils (clays). Correlation values of the simulated SVS soil moisture and the retrieved SAR soil moisture lie between 0.753–0.860 over sand and 0.676-0.865 over clay, with goodness of fit values between 0.567–0.739 and 0.457–0.748, respectively. The Root Mean Square Difference (RMSD) values range between 0.058–0.062 over sand and 0.055–0.113 over clay, with a maximum absolute bias of 0.049 and 0.094 over sand and clay, respectively. The unbiased RMSD values lie between 0.038–0.057 over sand and 0.039–0.064 over clay. Furthermore, results show an Index of Agreement (IA) between the simulated and the derived soil moisture always higher than 0.90.
MAG ID: 2920960378

Psychosocial Stress, Sedentary Behavior, and Physical Activity during Pregnancy among Canadian Women: Relationships in a Diverse Cohort and a Nationwide Sample - Sinclair, Isabelle; St-Pierre, Myriane; Elgbeili, Guillaume; Bernard, Paquito; Vaillancourt, Cathy; Gagnon, Sonia; Dancause, Kelsey Needham (International Journal of Environmental Research and Public Health, 2019)
Background: Past research shows that psychosocial stress and distress predict sedentary behavior and physical activity, but few studies focus on pregnant women. Our objective was to analyze relationships between psychosocial stress and distress with sedentary behavior and physical activity among pregnant women in Canada. Methods: We analyzed objectively-measured sedentary behavior and physical activity at 16–18, 24–26, and 32–24 weeks pregnancy in a sociodemographically diverse cohort of 70 women in Montreal, Canada. Participants completed the Perceived Stress Questionnaire and wore an accelerometer for 3 days that quantified sitting time and steps per day. We used univariate general linear models to analyze relationships between perceived stress with sedentary behavior and physical activity at each evaluation. To assess generalizability, we analyzed relationships between psychological distress with self-reported leisure-time sedentary behavior and daily energy expenditure in transportation and leisure physical activities among a sample representative of 166,095 women in the Canadian Community Health Survey. Results: In the Montreal cohort, we observed a positive association between perceived stress and sitting time, with small to moderate effect sizes (partial η2 = 0.08–0.16). We observed negative relationships between perceived stress and steps per day at the first two evaluations only, with small to moderate effect sizes (partial η2 = 0.08–0.11). Relationships for sedentary behavior were similar in the nationwide sample, but with smaller effect sizes (partial η2 = 0.02). There were no relationships between distress and physical activity in the nationwide sample. Conclusion: Psychosocial stress represents one risk factor for sedentarity, with relationships evident throughout pregnancy and at the population level. Relationships with physical activity are less consistent, but stress might represent a risk factor for low physical activity in early to mid-pregnancy. Results might guide the development of more comprehensive interventions targeting stress, sedentarity, and physical activity. In particular, integrating psychosocial health into interventions to reduce sedentarity, and including concrete guidelines on sedentary behavior in psychosocial health interventions, might be prioritized.

Social participation in older women and men: differences in community activities and barriers according to region and population size in Canada - Naud, Daniel; Généreux, Mélissa; Bruneau, Jean-François; Alauzet, Aline; Levasseur, Mélanie (BMC Public Health, 2019)
Social participation is a modifiable health determinant influenced by physical and social aspects of the environment. Little is known about aging women’s and men’s community activities and barriers according to region and population size. This study compared social participation, desire to participate more, and perceived barriers of aging women and men by Canadian region and population size.
Keywords: Généreux_Mélissa

Les impacts des changements climatiques sur la santé au Québec : l’exemple de l’Estrie - Petit, Geneviève; Lachance, Éric; Généreux, Mélissa; Barbeau-Meunier, Charles-Antoine; Pinsonneault, Linda; Dao, Huy Hao; Milot, Marie-Christine; Baron, Geneviève; Carignan, Alex (Le Climatoscope, 2019)
L’Organisation mondiale de la Santé (OMS) soutient que les changements climatiques représentent la plus grande menace pour la santé dans le monde au 21e siècle. Ceux-ci influencent négativement plusieurs déterminants sociaux et environnementaux de la santé comme l’accessibilité à la nourriture et la qualité de cette dernière, l’eau et l’air. Blessures, impacts psychosociaux, aggravation de maladies respiratoires, malnutrition, maladies infectieuses, décès : les conséquences sanitaires sont susceptibles d’affecter les populations sur tous les continents. Le Canada se réchauffe deux fois plus rapidement que la moyenne mondiale en raison de sa proximité au pôle Arctique, où le réchauffement est accéléré comparativement à l’équateur (Bush et Lemmen, 2019). Ainsi, le Québec n’est certainement pas à l’abri des changements climatiques. Dans le Sud de la province, les températures moyennes observées ont augmenté de plus d’un degré depuis 1970 et des répercussions se font déjà sentir dans notre environnement. Ce réchauffement, accompagné d’une plus grande variabilité du climat (augmentation du risque d’orages, de tempêtes et d’extrêmes hydrométéorologiques en général), représente un défi grandissant pour les professionnel.le.s de la santé. Dans la région de l’Estrie, les professionnel.le.s de santé publique ont effectué une analyse qui leur ont permis d’identifier quatre principaux problèmes environnementaux associés aux changements climatiques, soit : les vagues de chaleur; les inondations; les tiques à pattes noires; le pollen de l’herbe à poux. Ces problèmes ont des impacts importants sur la santé, c’est-à-dire potentiellement graves ou qui touchent un grand nombre de personnes. Le stress et les pertes (humaines et matérielles) engendrées par ces différents problèmes environnementaux peuvent aussi représenter une source majeure de problèmes psychologiques significatifs pouvant persister dans le temps. De plus, ces impacts sont variables selon les différents contextes sociaux des individus et des communautés, générant des inégalités sociales de santé.
Keywords: Généreux_Mélissa

Seniors Who Experienced the Lac-Mégantic Train Derailment Tragedy: What Are the Consequences on Physical and Mental Health? - Maltais, Danielle; Tremblay, Anne-Julie; Labra, Oscar; Fortin, Geneviève; Généreux, Mélissa; Roy, Mathieu; Lansard, Anne-Lise (Gerontology and Geriatric Medicine, 2019)
Introduction: In July 2013, a train derailment caused the death of 47 people and destroyed the downtown area in the city of Lac-Mégantic (Quebec, Canada). This tragedy had several impacts on this small community. Method: Three years after this disaster, we used a representative population-based survey conducted among 800 adults (including 265 seniors aged 65 or above) to assess the physical and mental health of seniors. Results: Several differences were observed in seniors’ physical and mental health based on their level of exposure to the tragedy. Nearly half of seniors highly exposed to the train derailment (41.7%) believe that their health has deteriorated in the past 3 years. The majority of seniors highly exposed to the train derailment (68.7%) also show symptoms of posttraumatic stress disorders. Seniors highly or moderately exposed to the tragedy were also more likely to have found positive changes in their personal and social life as compared with nonexposed seniors. Discussion: A technological disaster such as a train derailment still had negative impacts on seniors’ physical and mental health 3 years later. Conclusion: Public health authorities must tailor prevention and promotion programs to restore health and well-being in this population.
Keywords: Généreux_Mélissa

Responding to a Changing Climate: An Investigation of the Psychosocial Consequences of Climate Change and Community-based Mental Health Responses in High River - Hayes, K. (2019)
This dissertation explores the psychosocial consequences of climate change and psychosocial adaptation opportunities in High River, Alberta. Influenced by the theoretical approach of Political Ecology, I investigate community impacts and community-based mental health responses in High River following the 2013 Southern Alberta floods. Research methods include: a desktop climate change and health vulnerability and adaptation assessment that includes over 116 data sources; telephone interviews with key informant health and social services leaders (n = 14); four focus group sessions with front-line health and social services workers (n = 14); and, semi-structured interviews (n = 18) with a sample of community-members exposed to the 2013 flood and who self-identify in any one or more ways: female, youth, elderly, non-white, someone living in a low socio-economic status, someone with pre-existing health concerns. A total of 46 participants were recruited in this research. Results of the empirical investigation in High River are showcased in three manuscripts. The first manuscript, informed by critical Political Ecology, is an investigation of sociopolitical conditions that influence health inequities and adaptation opportunities (or lack thereof) in a changing climate in High River. The second is an empirical exploration of the long-term psychosocial consequences of the 2013 flood, relating these

Flood- and Weather-Damaged Homes and Mental Health: An Analysis Using England’s Mental Health Survey - Graham, Hilary; White, Piran; Cotton, Jacqui; McManus, Sally (International Journal of Environmental Research and Public Health, 2019)
There is increasing evidence that exposure to weather-related hazards like storms and floods adversely affects mental health. However, evidence of treated and untreated mental disorders based on diagnostic criteria for the general population is limited. We analysed the Adult Psychiatric Morbidity Survey, a large probability sample survey of adults in England (n = 7525), that provides the only national data on the prevalence of mental disorders assessed to diagnostic criteria. The most recent survey (2014–2015) asked participants if they had experienced damage to their home (due to wind, rain, snow or flood) in the six months prior to interview, a period that included months of unprecedented population exposure to flooding, particularly in Southern England. One in twenty (4.5%) reported living in a storm- or flood-damaged home in the previous six months. Social advantage (home ownership, higher household income) increased the odds of exposure to storm or flood damage. Exposure predicted having a common mental disorder over and above the effects of other known predictors of poor mental health. With climate change increasing the frequency and severity of storms and flooding, improving community resilience and disaster preparedness is a priority. Evidence on the mental health of exposed populations is key to building this capacity.
Keywords: Ouvrage_Collectif_Numéro1

Monitoring Adverse Psychosocial Outcomes One and Two Years After the Lac-Mégantic Train Derailment Tragedy (Eastern Townships, Quebec, Canada) - Généreux, Mélissa; Maltais, Danielle; Petit, Geneviève; Roy, Mathieu (Prehospital and Disaster Medicine, 2019)
Introduction:In July 2013, a train carrying 72 cars of crude oil derailed in the town of Lac-Mégantic (Eastern Townships, Quebec, Canada). This disaster provoked a major conflagration, explosions, 47 deaths, the destruction of 44 buildings, the evacuation of one-third of the local population, and an unparalleled oil spill. Notwithstanding the environmental impact, many citizens of this town and in surrounding areas have suffered and continue to suffer substantial losses as a direct consequence of this catastrophe.Problem:To tailor public health interventions and to meet the psychosocial needs of the community, the Public Health Department of Eastern Townships has undertaken repeated surveys to monitor health and well-being over time. This study focuses on negative psychosocial outcomes one and two years after the tragedy.Methods:Two cross-sectional surveys (2014 and 2015) were conducted among large random samples of adults in Lac-Mégantic and surrounding areas (2014: n = 811; 2015: n = 800), and elsewhere in the region (2014: n = 7,926; 2015: n = 800). A wide range of psychosocial outcomes was assessed (ie, daily stress, main source of stress, sense of insecurity, psychological distress, excessive drinking, anxiety or mood disorders, psychosocial services use, anxiolytic drug use, gambling habits, and posttraumatic stress symptoms [PSS]). Exposure to the tragedy was assessed using residential location (ie, six-digit postal code) and intensity of exposure (ie, intense, moderate, or low exposure; from nine items capturing human, material, or subjective losses). Relationships between such exposures and adverse psychosocial outcomes were examined using chi-squares and t-tests. Distribution of outcomes was also examined over time.Results:One year after the disaster, an important proportion of participants reported human, material, and subjective losses (64%, 23%, and 54%, respectively), whereas 17% of people experienced intense exposure. Participants from Lac-Mégantic, particularly those intensely exposed, were much more likely to report psychological distress, depressive episode, anxiety disorders, and anxiolytic drug use, relative to less-exposed ones. In 2015, 67% of the Lac-Mégantic participants (76% of intensely exposed) reported moderate to severe PSS. Surprisingly, the use of psychosocial services in Lac-Mégantic declined by 41% from 2014 to 2015.Conclusion:The psychosocial burden in the aftermath of the Lac-Mégantic tragedy is substantial and persistent. Public health organizations responding to large-scaling disasters should monitor long-term psychosocial consequences and advocate for community-based psychosocial support in order to help citizens in their recovery process.
Keywords: Généreux_Mélissa

From Science to Policy and Practice: A Critical Assessment of Knowledge Management before, during, and after Environmental Public Health Disasters - Généreux, Mélissa; Lafontaine, Marc; Eykelbosh, Angela (International Journal of Environmental Research and Public Health, 2019)
Canada regularly faces environmental public health (EPH) disasters. Given the importance of evidence-based, risk-informed decision-making, we aimed to critically assess the integration of EPH expertise and research into each phase of disaster management. In-depth interviews were conducted with 23 leaders in disaster management from Canada, the United States, the United Kingdom, and Australia, and were complemented by other qualitative methods. Three topics were examined: governance, knowledge creation/translation, and related barriers/needs. Data were analyzed through a four-step content analysis. Six critical success factors emerged from the analysis: blending the best of traditional and modern approaches; fostering community engagement; cultivating relationships; investing in preparedness and recovery; putting knowledge into practice; and ensuring sufficient human and financial resources. Several promising knowledge-to-action strategies were also identified, including mentorship programs, communities of practice, advisory groups, systematized learning, and comprehensive repositories of tools and resources. There is no single roadmap to incorporate EPH expertise and research into disaster management. Our findings suggest that preparation for and management of EPH disaster risks requires effective long-term collaboration between science, policy, and EPH practitioners at all levels in order to facilitate coordinated and timely deployment of multi-sectoral/jurisdictional resources when and where they are most needed.
Keywords: Généreux_Mélissa

Psychosocial Management Before, During, and After Emergencies and Disasters—Results from the Kobe Expert Meeting - Généreux, Mélissa; Schluter, Philip J.; Takahashi, Sho; Usami, Shiori; Mashino, Sonoe; Kayano, Ryoma; Kim, Yoshiharu (International Journal of Environmental Research and Public Health, 2019)
Emergencies and disasters typically affect entire communities, cause substantial losses and disruption, and result in a significant and persistent mental health burden. There is currently a paucity of evidence on safe and effective individual- and community-level strategies for improving mental health before, during, and after such events. In October 2018, the World Health Organization (WHO) Centre for Health Development (WHO Kobe Centre) convened a meeting bringing together leading Asia Pacific and international disaster research experts. The expert meeting identified key research needs in five major areas, one being “Psychosocial management before, during, and after emergencies and disasters”. Experts for this research area identified critical gaps in observational research (i.e., the monitoring of long-term psychological consequences) and interventional research (i.e., the development and evaluation of individual- and community-level interventions). Three key research issues were identified. First, experts underscored the need for a standardized and psychometrically robust instrument that classified the mental health/psychosocial risk of people within both a clinical and community setting. Then, the need for a standardization of methods for prevention, screening, diagnosis, and treatment for affected people was highlighted. Finally, experts called for a better identification of before, during, and after emergency or disaster assets associated with greater community resilience.
Keywords: Généreux_Mélissa

Impact of repeat flooding on mental health and health-related quality of life: a cross-sectional analysis of the English National Study of Flooding and Health - French, Clare E; Waite, Thomas D; Armstrong, Ben; Rubin, G. James; English National Study of Flooding and Health Study Group; Beck, Charles R; Oliver, Isabel (BMJ Open, 2019)
Objective To assess the association between flooding/repeat flooding and: (1) psychological morbidity (anxiety, depression, post-traumatic stress disorder (PTSD)) and (2) health-related quality of life (HRQoL) at 6 months post-flooding. Design Cross-sectional analysis of data from the English National Study of Flooding and Health. Setting Cumbria, England. Participants Questionnaires were sent to 2500 residential addresses at 6 months post-flooding; 590 people responded. Outcomes Probable depression was assessed using the Patient Health Questionnaire, probable anxiety using the Generalised Anxiety Disorder scale and probable PTSD using the short-form PTSD checklist (PCL-6). HRQoL was assessed using the EQ-5D-5L. Mental health outcomes were analysed using logistic regression; HRQoL dimensions using ordinal regression; and summary index/Visual Analogue Scale scores using linear regression. Results One hundred and nineteen participants had been flooded, over half of whom were experiencing a repeat flooding event (54%; n=64). Mental health outcomes were elevated among flooded compared with unaffected participants (adjusted OR for probable depression: 7.77, 95% CI: 1.51 to 40.13; anxiety: 4.16, 95% CI: 1.18 to 14.70; PTSD: 14.41, 95% CI: 3.91 to 53.13). The prevalence of depression was higher among repeat compared with single flooded participants, but this was not significant after adjustment. There was no difference in levels of anxiety or PTSD. Compared with unaffected participants, those flooded had lower EQ-5D-5L index scores (adjusted coefficient: −0.06, 95% CI: −0.12 to −0.01) and lower self-rated health scores (adjusted coefficient: −6.99, 95% CI: −11.96 to −2.02). There was, however, little difference in HRQoL overall between repeat and single flooded participants. Conclusions Interventions are needed to help minimise the impact of flooding on people’s mental health and HRQoL.
Keywords: Ouvrage_Collectif_Numéro1

Impacts psychosociaux négatifs des vagues de chaleur, des inondations, des feux de forêt et des tempêtes chez les travailleurs du Québec. - Adam-Poupart, A; Pouliot, L; Deger, L; Sassine, M.P; Coll, E.T (Institut national de santé publique du Québec (INSPQ), 2019)
Dans le cadre de la mise en œuvre du Plan d’action 2013-2020 sur les changements climatiques du Québec, le ministère de la Santé et des Services sociaux du Québec a mandaté l’Institut national de santé publique du Québec afin de mener une étude exploratoire portant sur les impacts psychosociaux vécus chez les travailleurs à la suite de quatre événements météorologiques extrêmes qui s’accentueront avec les changements climatiques, soit les vagues de chaleur, les inondations, les tempêtes et les feux de forêt. Cette étude exploratoire visait à examiner brièvement la littérature et les connaissances de différents acteurs-clés afin de proposer par la suite des projets de recherche plus importants et qui répondent aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec. Elle a mis en évidence que les événements météorologiques extrêmes étudiés peuvent entraîner des impacts psychosociaux chez les travailleurs, mais les connaissances sur ces impacts varient grandement selon l’événement. Les impacts psychosociaux chez les travailleurs ont été plus documentés dans la littérature scientifique pour les tempêtes et l’ont été de façon moins importante pour les inondations et les feux de forêt et négligeable pour les vagues de chaleur. Les travailleurs des services de la première ligne (comme les intervenants municipaux, les policiers, les pompiers, et les professionnels de la santé qui interviennent auprès des sinistrés, le personnel des services de travaux publics, etc.) et les agriculteurs font partie des populations de travailleurs qui ont été les plus étudiées. Les impacts psychologiques négatifs comme de l’épuisement, de la fatigue, de la détresse psychologique, de l’anxiété, de la colère et de la tristesse ont été plus souvent rapportés dans la littérature que les impacts sociaux. Il existe des facteurs de risque organisationnels (ex. : surcharge de travail, le manque de formation, de ressources matérielles, de personnels disponibles) et personnels (ex. : le fait d’être sinistré, le manque de contact avec les membres de la famille), communs à plusieurs événements et types de travailleurs, et qui peuvent aggraver les impacts psychosociaux vécus chez les travailleurs. Il existe aussi des facteurs de protection (ex. : reconnaissance ou gratitude, résilience individuelle, soutien social et efficacité collective). Il est important de consulter des acteurs clés pour bonifier les connaissances de la littérature scientifique. Dans le cadre de cette étude, les consultations avec des acteurs clés ont permis d’identifier de nouveaux travailleurs vulnérables, d’en apprendre davantage sur les caractéristiques de certains événements météorologiques extrêmes et de réaliser que les impacts psychosociaux vécus à la suite de ceux-ci pouvaient être positifs. L’acquisition de connaissances sur les impacts psychosociaux vécus chez les travailleurs à la suite des inondations est un des sujets qui répond aux besoins et aux enjeux des milieux de travail et de la santé publique au Québec.

Gray Zones: The Everyday Practices and Governance of Water beyond the Network - Truelove, Yaffa (Annals of the American Association of Geographers, 2019)
Keywords: Ouvrage_Collectif_Numéro1

A decision-support tool to increase urban resilience to flood risk: from a theoretical concept to operational urban managers re-appropriation. A France-Quebec comparative approach - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (2019)
Published: Fifth World Congress on Risk - Society for Risk Analysis
Keywords: Hémond_Yannick

Collaborative governance of essential systems risk assessment approach - Lépine, C.; Baril, G.; Therrien, M.-C.; Hémond, Yannick; Robert, Benoît (2019)
Keywords: Hémond_Yannick

Psychosocial vulnerability and demographic characteristics in extreme flash floods: The case of Mandra 2017 flood in Greece - Speis, Phoebe-Demeter; Andreadakis, Emmanuel; Diakakis, Michalis; Daidassi, Evanthia; Sarigiannis, Georgios (International Journal of Disaster Risk Reduction, 2019)
Keywords: Ouvrage_Collectif_Numéro1

Spatial Analysis of Social Vulnerability to Floods Based on the MOVE Framework and Information Entropy Method: Case Study of Katsushika Ward, Tokyo - Lianxiao; Morimoto, Takehiro (Sustainability, 2019)
Tokyo is located in a lowland area that is vulnerable to flooding. Due to global climate change, the scalability and frequency of flooding is increasing. On the other hand, population aging and family structural changes, as well as the lack of adaptation measures, would accelerate flooding vulnerability. The key factors involved in social vulnerability must be studied to reduce the risk of flooding. In this study, we refer to the MOVE framework (a disaster vulnerability assessment framework) and analyze it from three perspectives: Exposure to social vulnerability, susceptibility, and resilience. We subsequently develop an index system to complete the evaluation using 11 indicators. The collected data will help reveal social vulnerability to floods in the Katsushika Ward, Tokyo, using the information entropy method and GIS. We found that the western region of the Katsushika Ward is at more risk than the eastern region during flooding. Additionally, the possibility of a serious crisis erupting is greater in the southwestern region than in the northwestern region. Consequently, we conclude that the spatial distribution of flooding varies in the region. The results of this study will help in understanding social vulnerability, in selecting and combining adaptation measures suited to the characteristics of the area, and in the effective and efficient implementation of these measures by the local government’s disaster department.

Risques d’inondation et vulnérabilité : l’exemple du bassin versant de la rivière Kennebecasis, Nouveau-Brunswick, Canada. - Fortin, Guillaume; Poirier, Charlotte; Duhamel, Françis; Germain, Daniel (2019)
La province du Nouveau-Brunswick, situee dans l’est du Canada, est tres affectee par les inondations. Bien que moins documentee que l’alea, la dimension humaine du risque que represente la vulnerabilite est importante pour l’adaptation des populations. Cet article fait un survol des principaux concepts lies a la vulnerabilite et presente leur application a l’echelle d’un bassin versant de taille moyenne. Les resultats montrent la necessite de considerer simultanement la perception et la preparation au risque d’inondation. En effet, si certains residents dans les zones a risque ont une bonne connaissance des inondations et une perception realiste du risque, cela ne se traduit pas necessairement par une preparation adaptee et adequate face au risque. La reduction du risque passe indeniablement par une meilleure sensibilisation et education de la population.
MAG ID: 3012134137

A GIS Tool for Mapping Dam-Break Flood Hazards in Italy - Albano, Raffaele; Mancusi, Leonardo; Adamowski, Jan; Cantisani, Andrea; Sole, Aurelia (ISPRS International Journal of Geo-Information, 2019)
Mapping the delineation of areas that are flooded due to water control infrastructure failure is a critical issue. Practical difficulties often present challenges to the accurate and effective analysis of dam-break hazard areas. Such studies are expensive, lengthy, and require large volumes of incoming data and refined technical skills. The creation of cost-efficient geospatial tools provides rapid and inexpensive estimates of instantaneous dam-break (due to structural failure) flooded areas that complement, but do not replace, the results of hydrodynamic simulations. The current study implements a Geographic Information System (GIS) based method that can provide useful information regarding the delineation of dam-break flood-prone areas in both data-scarce environments and transboundary regions, in the absence of detailed studies. Moreover, the proposed tool enables, without advanced technical skills, the analysis of a wide number of case studies that support the prioritization of interventions, or, in emergency situations, the simulation of numerous initial hypotheses (e.g., the modification of initial water level/volume in the case of limited dam functionality), without incurring high computational time. The proposed model is based on the commonly available data for masonry dams, i.e., dam geometry (e.g., reservoir capacity, dam height, and crest length), and a Digital Elevation Model. The model allows for rapid and cost-effective dam-break hazard mapping by evaluating three components: (i) the dam-failure discharge hydrograph, (ii) the propagation of the flood, and (iii) the delineation of flood-prone areas. The tool exhibited high accuracy and reliability in the identification of hypothetical dam-break flood-prone areas when compared to the results of traditional hydrodynamic approaches, as applied to a dam in Basilicata (Southern Italy). In particular, the over- and under-estimation rates of the proposed tool, for the San Giuliano dam, Basilicata, were evaluated by comparing its outputs with flood inundation maps that were obtained by two traditional methods whil using a one-dimensional and a two-dimensional propagation model, resulting in a specificity value of roughly 90%. These results confirm that most parts of the flood map were correctly classified as flooded by the proposed GIS model. A sensitivity value of over 75% confirms that several zones were also correctly identified as non-flooded. Moreover, the overall effectiveness and reliability of the proposed model were evaluated, for the Gleno Dam (located in the Central Italian Alps), by comparing the results of literature studies concerning the application of monodimensional numerical models and the extent of the flooded area reconstructed by the available historical information, obtaining an accuracy of around 94%. Finally, the computational efficiency of the proposed tool was tested on a demonstrative application of 250 Italian arch and gravity dams. The results, when carried out using a PC, Pentium Intel Core i5 Processor CPU 3.2 GHz, 8 GB RAM, required about 73 min, showing the potential of such a tool applied to dam-break flood mapping for a large number of dams.